Encyclopedia of Life Sciences 2019
DOI: 10.1002/9780470015902.a0003375.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and the Brain

Abstract: Anatomical, neurochemical and functional properties of the mammalian brain change with age, and the trajectories of ageing are modified by many genetic and environmental risk factors, including lifestyle variables. Age‐related changes do not reflect a specific cellular program, but fundamental changes precipitating intracellular accumulation of reactive oxygen species and diminishing energy production may underlie age‐related deterioration of the brain structure and information processing properties. The latte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The natural history of myelination across the human lifespan closely tracks cognitive capacity [6, 7]. Cortical myelin, in particular in frontal lobes, does not fully mature in humans until their late-thirties [8, 9]. Afterwards myelination regresses and this naturally occurring age-related loss is accelerated in AD [10].…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of myelination across the human lifespan closely tracks cognitive capacity [6, 7]. Cortical myelin, in particular in frontal lobes, does not fully mature in humans until their late-thirties [8, 9]. Afterwards myelination regresses and this naturally occurring age-related loss is accelerated in AD [10].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to age-related memory impairments, the hippocampal formation, that is, dentate gyrus (DG), cornu Ammonis (CA) fields, and subiculum, warrants particular attention as it is critically involved in memory processing and is affected early in the progression of Alzheimer's disease (AD). Magnetic resonance imaging (MRI) studies have, for example, shown reductions in total hippocampal volume associated with aging in cognitively healthy individuals ( Raz, 2001 ), while hippocampal atrophy remains one of the supporting diagnostic features of amnestic Mild Cognitive Impairment (aMCI) and AD ( de Flores et al., 2015a ). The next challenge is to distinguish normal age-related hippocampal changes from potential pathological changes related to genetic and lifestyle risk factors of dementia in pre-symptomatic individuals ( Jack et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to age-related memory impairments, the hippocampal formation, i.e., dentate gyrus, cornu Ammonis (CA) fields, and subiculum, warrants particular attention as it is critically involved in memory processing and is affected early in the progression of Alzheimer’s disease (AD). Magnetic resonance imaging (MRI) studies have, for example, shown reductions in total hippocampal volume associated with aging in cognitively healthy individuals (Raz, 2001), while hippocampal atrophy remains one of the supporting diagnostic features of amnestic Mild Cognitive Impairment (aMCI) and AD (de Flores et al, 2015a). The next challenge is to distinguish normal age-related hippocampal changes from potential pathological changes related to genetic and lifestyle risk factors of dementia in pre-symptomatic individuals (Jack et al, 2013).…”
Section: Introductionmentioning
confidence: 99%